2022
DOI: 10.3389/fnhum.2022.727565
|View full text |Cite
|
Sign up to set email alerts
|

The Multidisciplinary Guidelines for Diagnosis and Referral in Cerebral Visual Impairment

Abstract: IntroductionCerebral visual impairment (CVI) is an important cause of visual impairment in western countries. Perinatal hypoxic-ischemic damage is the most frequent cause of CVI but CVI can also be the result of a genetic disorder. The majority of children with CVI have cerebral palsy and/or developmental delay. Early diagnosis is crucial; however, there is a need for consensus on evidence based diagnostic tools and referral criteria. The aim of this study is to develop guidelines for diagnosis and referral in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 131 publications
(286 reference statements)
1
13
0
Order By: Relevance
“…Most children with CVI are developmentally delayed, and early diagnosis is crucial for rehabilitating these children. 11 In our study, CVI was seen in 65 children (21.6%). Damage to the visual parts of the brain due to any cause such as premature birth, insufficient oxygenation, antenatal or postnatal infection of the baby, brain malformation, hydrocephalus, seizure in infant life, and metabolic disease can result in CVI.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Most children with CVI are developmentally delayed, and early diagnosis is crucial for rehabilitating these children. 11 In our study, CVI was seen in 65 children (21.6%). Damage to the visual parts of the brain due to any cause such as premature birth, insufficient oxygenation, antenatal or postnatal infection of the baby, brain malformation, hydrocephalus, seizure in infant life, and metabolic disease can result in CVI.…”
Section: Discussionsupporting
confidence: 47%
“…Undetected visual impairment combined with other handicaps is likely to have an adverse effect on development and may lead to an underestimation of intellectual ability. 11 Early identification of ocular findings in children with developmental delay helps to prevent or mitigate any adverse effects on visual and overall development, thus improving the quality of life. Ocular issues also affect a child's ability to learn and perform in school.…”
Section: Discussionmentioning
confidence: 99%
“…All participants with CVI were previously diagnosed by eyecare professionals with extensive clinical experience working with this population. Diagnosis was based on a directed and objective assessment of visual functions (including visual acuity, contrast, visual field perimetry, color, and ocular motor functions), functional vision assessment (use of surveys, questionnaires, and activities), a thorough refractive and ocular examination, as well as an integrated review of medical history and available neuroimaging and electrophysiology records 4,10,21 . Causes of CVI were diverse and included hypoxic–ischemic injury related to preterm birth, periventricular leukomalacia, hypoxic–ischemic encephalopathy, seizure disorder, as well as genetic and metabolic disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Hypoxicischemic Encephalopathy (HIE), Epilepsy, and Cerebral Palsy (CP) suggested that visual improvement over time was unlikely; more positively, interventions using physical therapy, occupational therapy, and refractive correction were associated with long-term visual improvement [14]. Early diagnosis is crucial [15] to allow for these interventions, and its standardization is necessary given the array of tests in current use. Five particularly important parameters are 1) Medical History; 2) Ophthalmological and Orthoptic assessment; 3) Neuropsychological assessment; 4) Neuroradiology and MRI; 5) Genetic Assessment.…”
Section: Commentarymentioning
confidence: 99%